Simulations of “tunnelling of the 3rd kind” - Mou, Zong-Gang; Saffin, Paul M.; Tognarelli, Paul; Tranberg, Anders (Springer, 2017)
We consider the phenomenon of ``tunnelling of the 3rd kind" \cite{third}, whereby a magnetic field may traverse a classically impenetrable barrier by pair creation of unimpeded quantum fermions. These propagate through the barrier and generate a magnetic field on the other side. We study this numerically using quantum fermions coupled to a classical Higgs-gauge system, where we set up a magnetic field outside a box shielded by two superconducting barriers. We examine the magnitude of the internal magnetic field, and find agreement with existing perturbative results within a factor of two.